Lattice dynamics and thermoelectric properties of nanocrystalline silicon–germanium alloys. Issue 3 (26th October 2015) - Claudio, Tania; Stein, Niklas; Petermann, Nils; Stroppa, Daniel G.; Koza, Michael Marek; Wiggers, Hartmut; Klobes, Benedikt; Schierning, Gabi; Hermann, Raphaël P.
Abstract: The lattice dynamics and thermoelectric properties of sintered phosphorus‐doped nanostructured silicon–germanium alloys obtained by gas‐phase synthesis were studied. Measurements of the density of phonon states by inelastic neutron scattering were combined with measurements of the elastic constants and the low‐temperature heat capacity. A strong influence of nanostructuring and alloying on the lattice dynamics was observed. The thermoelectric transport properties of samples with different doping as well as samples sintered at different temperature were characterized between room temperature and 1000 ° C. A peak figure of merit zT = 0.88 at 900 ° C is observed and is comparatively insensitive to the aforementioned parameter variations.